Practical application of bioelectric research of biologically active centers for the assessment of sheep wool productivity - Samusenko Liudmila (EDP Sciences, 2021)
The intensification of sheep wool production requires development of new methods for assessing the quality of products based on the knowledge of the functional state of the body, life support mechanisms and the formation of products in the process of its synthesis. Such functional systems include a complex of superficially localized biologically active centers (SLBACs) of animals, which serve as sensory regulatory formations involved in providing compensatory adaptive reactions of the animal organism. The research was carried out on sheep of the North Caucasian breed and the North Caucasian and the Romanov cross-breeds (3/4 R x 1/4 NC). The aim of the research was to clarify the possibility of assessing the wool productivity of sheep of different breeds according to the level of the bioenergetic potential (LBP) of their superficially localized biologically active centers. The studies were carried out on sheep of the North Caucasian breed and their crossbreeds with the Romanov breed (3/4 R x 1/4 NC). The object of the research was 6- and 8-month-old ewe hoggs and adult purebred ewes of the North Caucasian breed at the age of 2 years old. It was found out that sheep of different breeds and ages have different LBP of the SLBACs, and the value of the biopotential can be used to assess the quantitative and qualitative properties of wool in the comparable units. Based on the established dependencies, a method for determining a sheep wool classing has been developed. This method eliminates the need to use complex laboratory equipment and reduces time for the wool research.